2005
DOI: 10.1164/rccm.200409-1284oc
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of the Hypoplastic Lung by Prenatal Cyclical Strain

Abstract: We determined the effects of sustained and cyclical prenatal mechanical strain on the hypoplastic lung of the ovine model of congenital diaphragmatic hernia. Over a period of 4 weeks in late gestation, repeated cyclical tracheal occlusion for 23 hours with 1-hour release stimulated minimal growth, but promoted maturation with the development of a saccular lung. In contrast, a cycle consisting of 47 hours with 1-hour release induced optimal lung growth and morphologic maturation of the hypoplastic lung parenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 72 publications
2
34
0
1
Order By: Relevance
“…However, even after correction for gestational age at birth, early prenatal balloon removal improved the chances of survival. In animal experiments, cyclical or temporary occlusion has been shown to improve lung maturation 26,27,31 . This might also be the case clinically, although early morbidity parameters were unaffected by prenatal balloon removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even after correction for gestational age at birth, early prenatal balloon removal improved the chances of survival. In animal experiments, cyclical or temporary occlusion has been shown to improve lung maturation 26,27,31 . This might also be the case clinically, although early morbidity parameters were unaffected by prenatal balloon removal.…”
Section: Discussionmentioning
confidence: 99%
“…The FETO procedure has been described in detail 22,23,28 . Briefly it consists of the percutaneous fetoscopic insertion of a balloon into the fetal trachea, which in general is performed at approximately 26-28 (range, [23][24][25][26][27][28][29][30][31][32][33] weeks' gestation. The balloon is preferentially removed in utero at approximately 34 weeks by tracheoscopy or ultrasound-guided puncture.…”
Section: Methodsmentioning
confidence: 99%
“…Fetal breathing movements allow the fluid to exit the airways, leveling that pressure. This results in periods of tissue stretch, its cyclical nature being important for an appropriate balance between growth and differentiation (Nelson et al, 2005). Surgical tracheal occlusion (TO) takes advantage of this principle, its effects being a function of the timing and duration.…”
Section: Consequences Of Prenatal Assessment and Interventions Improvmentioning
confidence: 99%
“…Nelson later demonstrated that best results were obtained with a protocol of 47 h of occlusion alternated with 1 h of release. He did this between 110 (cannalicular phase) and 138 days of ovine gestation (saccular; term = 145 days; Figure 4) (Nelson et al, 2005).…”
Section: Consequences Of Prenatal Assessment and Interventions Improvmentioning
confidence: 99%
“…Com a realização dos experimentos em animais e humanos, começou-se a observar que, apesar de a oclusão endotraqueal fetal promover aumento na massa pulmonar e melhorar as trocas gasosas, ela também impedia o desenvolvimento e maturação dos pneumócitos do tipo II nos alvéolos, bem como a produção de surfactante alveolar 45 . Assim, começou a se propor que a oclusão traqueal fetal fosse revertida ainda no período intrauterino 46 .…”
Section: Iii) Oclusão Endotraqueal Fetal Na Hérnia Diafragmática Congunclassified